Post‐therapy plasma concentrations of quetiapine in Taiwanese patients - Cho‐Yin Huang; Yen‐Feng Lin; Chia‐Ru Chen; Shih‐Ku Lin (Wiley, 2023)
Abstract Aims Quetiapine is widely used to treat psychiatric disorders such as major depression, generalized anxiety disorder, dysthymic disorder, and insomnia other than schizophrenia and bipolar disorder. This study investigated the diagnostic distribution of quetiapine use in patients in a psychiatric hospital, the doses of quetiapine prescribed, and the plasma concentrations (Cps) of quetiapine and active metabolites. Methods We enrolled 107 patients who had been prescribed quetiapine for at least 4 weeks. Diagnoses, demographics, and concomitant medications were recorded. Blood sampling was performed in the morning, approximately 12 h after the before‐bed dose of quetiapine. Results Diagnoses comprised schizophrenia (n = 25), bipolar disorder (n = 51), major depression (n = 15), dysthymic disorder (n = 9), and others (n = 7). The daily dose (DD) of quetiapine ranged from 25 to 800 (175.9 ± 184.4) mg, with the mean Cp being 105.6 ± 215.3 ng/ml, with a mean Cps/DD ratio of 0.58 ± 0.55 ng/ml/mg. There was a moderate positive linear correlation between the dose and Cps of quetiapine (r = 0.60), and the interpatient variation in Cps/DD ratio was up to 26‐fold. Conclusion Quetiapine is used in various doses to treat many psychiatric disorders other than psychosis, and it is usually prescribed as a secondary antipsychotic for symptoms such as insomnia or agitation. A wide interpatient variation of the Cps/DD ratio was noticed. Patients of East Asian descent may exhibit a 50% to 100% increase in the Cps/DD ratio for quetiapine compared with patients of Western descent.